THE STRUGGLE OF WOMEN’S CHARACTER AGAINST PATRIARCHAL TRADITION IN QUEEN CHARLOTTE BY TOM VERICA - Fauziah, Afifah Nur Rizki; EF, Abd. Hanan; Assiddiqi, Hasbi (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study examines the resistance of female characters against patriarchal traditions in Queen Charlotte: A Bridgerton Story. The research explores how gender, race, and social status shape the struggles of Queen Charlotte, Lady Danbury, and Princess Augusta in navigating patriarchal constraints such as social expectations, legal limitations, and political hierarchies. Employing a qualitative descriptive method with close reading and thematic analysis, this study investigates the characters’ different strategies of resistance—negotiation, rejection, and manipulation—within the monarchical system. The findings reveal that while Queen Charlotte negotiates power within the constraints of patriarchy, Lady Danbury outright rejects traditional gender roles, and Princess Augusta manipulates the system for survival. The study also highlights how the series reconstructs history through a modern feminist lens, emphasizing gender agency and racial inclusivity over strict historical accuracy. This research contributes to feminist literary criticism by demonstrating how historical fiction serves both as a critique of systemic oppression and as a medium for narratives of resistance, reinforcing the ongoing discourse on gender equality and intersectionality in media representation.